2021
DOI: 10.3390/ani11123448
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Applications and Factors Involved in Validating Thermal Windows Using Infrared Thermography to Assess the Health and Thermostability of Laboratory Animals

Abstract: Evaluating laboratory animals’ health and thermostability are fundamental components of all experimental designs. Alterations in either one of these parameters have been shown to trigger physiological changes that can compromise the welfare of the species and the replicability and robustness of the results obtained. Due to the nature and complexity of evaluating and managing the species involved in research protocols, non-invasive tools such as infrared thermography (IRT) have been adopted to quantify these pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 93 publications
3
39
0
Order By: Relevance
“…Duparcq et al, [ 37 ] observed that the maximum eye temperature peaked within 1 min, while tail temperature dropped to its lowest at around 2 min after exposure to a novel environment. Drop in tail temperature lasting for at least 2 min was observed also in our study, with this short-term vasoconstriction resulting in reduction of heat dissipated through the tail surface [ 22 ]. This initial drop in temperature can, during prolonged stress exposure, be followed by an increase in tail temperature [ 17 ], as a means to dissipate excess heat [ 22 ].…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Duparcq et al, [ 37 ] observed that the maximum eye temperature peaked within 1 min, while tail temperature dropped to its lowest at around 2 min after exposure to a novel environment. Drop in tail temperature lasting for at least 2 min was observed also in our study, with this short-term vasoconstriction resulting in reduction of heat dissipated through the tail surface [ 22 ]. This initial drop in temperature can, during prolonged stress exposure, be followed by an increase in tail temperature [ 17 ], as a means to dissipate excess heat [ 22 ].…”
Section: Discussionsupporting
confidence: 68%
“…Drop in tail temperature lasting for at least 2 min was observed also in our study, with this short-term vasoconstriction resulting in reduction of heat dissipated through the tail surface [ 22 ]. This initial drop in temperature can, during prolonged stress exposure, be followed by an increase in tail temperature [ 17 ], as a means to dissipate excess heat [ 22 ]. We believe that the increase in T tail of the third animal tested during the DH test provides support for this explanation.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Identifying between-species differences and determining the thermal comfort ranges of specific animal species is mediated by neurons in the central nervous system (CNS) and peripheral receptors [ 15 , 16 ]. Thermosensitive receptors exist in both prokaryotic and eukaryotic organisms [ 17 ].…”
Section: Introductionmentioning
confidence: 99%